STRUCTURE-BASED DRUG DESIGNING STUDIES TOWARDS EXPLORING THE POTENTIAL ANTICANCER ACTIVITY OF SELECTED PHYTOCOMPOUNDS AGAINST HISTONE DEACETYLASE 10 PROTEIN - M, Sabeena; Jamil, Kaiser; Avn, Swamy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Histone deacetylases (HDACs) are proteins which play a crucial role in cell growth, maintenance, and regulation. Abnormal HDAC proteins produced by genetic mutations are common in human cancers. HDAC10 is a class II HDAC member, and its expression in many cancers has been documented. The aim of this study was to determine the best docking of phytocompounds selected from a list of such compounds in the database of chemicals for HDAC10. Methods: The crystal structure of HDAC10 was retrieved from Protein Data Bank and prepared for docking studies by post-translational modification (PTM) analysis. Then, we have screened 450 phytocompounds for molecular docking studies and determined their binding affinities against HDAC10 by using PatchDock server. Results: The PTM analysis showed that myristoylation sites were more abundant in HDAC10 which might be important functional sites for the gene regulation. The results revealed the receptor/inhibitor interactions within an active domain consisting of 30 important amino acid residues. Affinity-based studies have indicated the docking energy levels by calculating hydrogen bonding, steric, and hydrophobic interactions. Among the inhibitors, we could shortlist four compounds which showed excellent binding affinity. Hence, we evaluated drug binding affinities of these four compounds and determined their atomic contact energy values. Analysis of the docking results showed holacurtine>periplogenin>3,3'-diindolylmethane>epigallocat echin as the order of binding affinities, with holacurtine having the best docking score. Conclusion: It is proposed from these studies that the docking and scoring methods could be useful for selecting and shortlisting the promising antitumor molecules. These molecules could be further tested using in vitro and in vivo methods to confirm their role in HDAC10-associated cancers. Furthermore, myristoylation sites in HDAC10 could form an important binding site for selecting hit inhibitor compounds. The PTM studies together with the binding mode analysis facilitate the protein-protein interaction studies of HDAC10, and thioredoxin-interacting protein is considered as one of the transcriptional regulators of HDAC10.